1989
DOI: 10.1002/lsm.1900090513
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage responsiveness to light therapy

Abstract: Macrophages are a source of many important mediators of wound repair. It was the purpose of this study to see if light could stimulate the release of these mediators. In this study an established macrophage-like cell line (U-937) was used. The cells were exposed in culture to the following wavelengths of light: 660 nm, 820 nm, 870 nm, and 880 nm. The 820-nm source was coherent and polarised, and the others were non-coherent. Twelve hours after exposure the macrophage supernatant was removed and placed on 3T3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
1
19

Year Published

1990
1990
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(166 citation statements)
references
References 17 publications
3
142
1
19
Order By: Relevance
“…The beneficial effects of red light on the skin have been suggested by many studies [35][36][37][38][39][40][41][42][43][44][45]. It has been demonstrated by an in vitro study that red light influenced cytokine release from macrophages, which consequently stimulated fibroblast proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of red light on the skin have been suggested by many studies [35][36][37][38][39][40][41][42][43][44][45]. It has been demonstrated by an in vitro study that red light influenced cytokine release from macrophages, which consequently stimulated fibroblast proliferation [35].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated by an in vitro study that red light influenced cytokine release from macrophages, which consequently stimulated fibroblast proliferation [35]. Karu [38,39] suggested that absorption of red and near-infrared light by photoacceptor molecules within the respiratory chains can cause alteration in the redox status of the cells and activate the nucleic acid synthesis to accelerate cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…LLLT can also induce collagen synthesis and growth factor secretion. Furthermore, there is also a downregulation of the production of pro-inflammatory cytokines and cell apoptosis by LLLT [14][15][16][17][18][19][20].…”
Section: Lllt-mechanism Of Action On Cellular and Tissular Levelmentioning
confidence: 99%
“…It has been demonstrated 8,9 that lasers operating at different wavelengths activate the macrophages to release factors that stimulate fibroblast proliferation. Low-intensity laser acts on the synthesis and collagen remodeling, fibroblast number, diameter, and tensile strength of the treated wounds 7 .…”
Section: Introductionmentioning
confidence: 99%